Enhancing Emergency Fracture Diagnosis with Point-of-Care Ultrasound (Pocus) : A Rapid and Efficient Alternative: A Literature Review - Agastya, Wayan Dhea; Rahmadinie, Amalia; Aulia, Khansa Tsabitah; Anrofi, Fakhirah Nailah; Al Habsyi, Alya Raguan; Firdausiyah, Shofie Ayu Nur; Winangest, Bisarda Kanira Permata Putri (Journal of Diverse Medical Research: Medicosphere, 2025)
Abstract Introduction: Fracture diagnosis is a crucial aspect of trauma and musculoskeletal injury management, traditionally relying on imaging modalities such as X-ray, CT scan, and MRI. However, these methods have limitations, including high costs, long waiting times, radiation exposure, and limited accessibility in remote areas. Point-of-Care Ultrasound (POCUS) has emerged as a diagnostic alternative that is more portable, cost-effective, radiation-free, and provides real-time results, making it a potential solution in emergency situations or resource-limited healthcare facilities. Methods: This study employs a literature search approach based on the PICO framework to evaluate the effectiveness of Point-of-Care Ultrasound (POCUS) in detecting fractures compared to X-ray, CT scan, and MRI. Literature sources were obtained from Scopus, ScienceDirect, Google Scholar, and PubMed using relevant keywords. Seven English-language journals were selected for further analysis. Results and Disscussion: POCUS is a rapid, non-invasive, and effective diagnostic tool for fracture and musculoskeletal injury. It allows fracture identification within an average of 3.9 minutes, with a sensitivity exceeding 85%, reaching up to 100% in children, while its specificity exceeds 90%. Although its accuracy is still lower than that of MRI, POCUS excels in terms of speed and patient convenience. Conclusion: POCUS serves as a safe and rapid alternative to conventional methods, particularly for children and patients with limited access to radiographic imaging. It provides a more patient-friendly diagnostic method, especially in medical settings requiring high safety and speed. While X-ray remains the gold standard, POCUS can be utilized in emergency situations. However, its effectiveness depends on operator skill and is less optimal for detecting complex fractures. Keywords: Point-of-Care-Ultrasound, POCUS, Fracture, Diagnosis, Medical Imaging